Ectopic Runx1 expression rescues Tal-1-deficiency in the generation of primitive and definitive hematopoiesis. - Julia Tornack; Katharina Seiler; Andreas Grützkau; Joachim R Grün; Masafumi Onodera; Fritz Melchers; Motokazu Tsuneto (PLoS ONE, 2013)
The transcription factors SCL/Tal-1 and AML1/Runx1 control the generation of pluripotent hematopoietic stem cells (pHSC) and, thereby, primitive and definitive hematopoiesis, during embryonic development of the mouse from mesoderm. Thus, Runx1-deficient mice generate primitive, but not definitive hematopoiesis, while Tal-1-deficient mice are completely defective. Primitive as well as definitive hematopoiesis can be developed "in vitro" from embryonic stem cells (ESC). We show that wild type, as well as Tal-1(-/-) and Runx1(-/-) ESCs, induced to differentiation, all expand within 5 days to comparable numbers of Flk1(+) mesodermal cells. While wild type ESCs further differentiate to primitive and definitive erythrocytes, to c-fms(+)Gr1(+)Mac1(+) myeloid cells, and to B220(+)CD19(+) B- and CD4(+)/CD8(+) T-lymphoid cells, Runx1(-/-) ESCs, as expected, only develop primitive erythrocytes, and Tal-1(-/-) ESCs do not generate any hematopoietic cells. Retroviral transduction with Runx1 of Runx1(-/-) ESCs, differentiated for 4 days to mesoderm, rescues definitive erythropoiesis, myelopoiesis and lymphopoiesis, though only with 1-10% of the efficiencies of wild type ESC hematopoiesis. Surprisingly, Tal-1(-/-) ESCs can also be rescued at comparably low efficiencies to primitive and definitive erythropoiesis, and to myelopoiesis and lymphopoiesis by retroviral transduction with Runx1. These results suggest that Tal-1 expression is needed to express Runx1 in mesoderm, and that ectopic expression of Runx1 in mesoderm is sufficient to induce primitive as well as definitive hematopoiesis in the absence of Tal-1. Retroviral transduction of "in vitro" differentiating Tal-1(-/-) and Runx1(-/-) ESCs should be a useful experimental tool to probe selected genes for activities in the generation of hematopoietic progenitors "in vitro", and to assess the potential transforming activities in hematopoiesis of mutant forms of Tal-1 and Runx1 from acute myeloid leukemia and related tumors.